Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Sekolah Tinggi Serasan - Aryani, Dwi Oktarina (Jurnal Ilmu Manajemen, 2011)
The purpose of this study is to examine theimpact of organisation culture and leadershiptyle toward employee peformance in sekolah tinggi serasan muara enim simultaneously and partially, in which causalty is used as a research design.The variables used are organization culture, leadership style and employee peformance.Population is 35 employees. Data collected convert the data from ordinal to interval, the regression analysis is conducted.There is an impact of organization culture and leadership style toward employee peformance Based on the analysis that F<p value therefore Ho is rejected, means that organization culture and leadership style have an impact toward employee peformance both simultaneously and partialy. R.coefficient is 0,631, means that 63,1% of both independent variables could explain the employee performance